IMPACT OF THE MILITARY ACTIONS IN UKRAINE ON THE ECOSYSTEM OF UKRAINE - Орєшков, Василь; Гинда, Валентина; Бугеда, Любов (SWorldJournal, 2025)
The article examines the environmental consequences of the full-scale war launched by the Russian Federation against Ukraine. Particular attention is paid to the massive use of missile weapons and their impact on air, soil, and water resources. The main